Sistem Informasi Akuntansi Simpan Pinjam Pada Sinar Kalimantan Dengan Metode Pengembangan Waterfall - Nanda Diaz Arizona; Ety Susilowati (Jurnal Sistem Informasi Akuntansi, 2021)
Sinar Kalimantan Cooperative is a community service cooperative in savings and loans. Based on the analysis that has been done, the Sinar Kalimantan Cooperative still recaps each per each cash-in and cash-out data transactions that come from notes and then copy them to Ms. Excel to be used as financial statements. Processing data like this requires effort and a long time, errors in data processing that have an impact on the quality of information in financial statements. Therefore, the purpose of writing this Final Project is to design and build a web-based savings and loan accounting information system at the Sinar Kalimantan Cooperative using the waterfall model as a software development method consisting of analysis of software requirements, design, program code creation and testing. Data collection techniques used consisted of observation, interviews and literature study. This system is built to provide facilities for two users, namely the Chairman and the Cashier. Chairman can manage employee (user) data, access loan reports, loan list reports, installment reports, savings reports, general journal reports, general ledger reports, balance sheet reports, cash receipts reports, cash disbursements reports and cash flow report. The cashier can manage account data, customer data, deposit data, deposit withdrawal data, loan data, installment data and expense (cost) data and access loan reports, loan list reports, installment reports and savings reports. The savings and loan accounting information system that was built is expected to help improve the performance of savings and loan data processing at the Sinar Kalimantan Cooperative.